2020
DOI: 10.3892/mmr.2020.11761
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf‑1/cysteine‑rich angiogenic inducer 61 axis mediates palmitic acid‑induced inflammation and apoptosis of vascular endothelial cells

Abstract: Cardiovascular diseases (CVDs) are a major cause of mortality around the world, and the presence of atherosclerosis is the most common characteristic in patients with CVDs. Cysteine-rich angiogenic inducer 61 (CCN1) has been reported to serve an important role in the pathogenesis of atherosclerotic lesions. The aim of the present study was to investigate whether CCN1 could regulate the inflammation and apoptosis of endothelial cells induced by palmitic acid (PA). Dickkopf-1 (DKK1) is an important antagonist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Knockdown of cysteine-rich angiogenesis inducer (CCN1) could reduce the induction of EC inflammation and apoptosis by PA through inactivation of Wnt/β-catenin. 272 Low stress activates Wnt/β-catenin and promotes endothelial mesenchymal transition (EndMT). 273 …”
Section: Signaling Pathways In Atherosclerosismentioning
confidence: 99%
“…Knockdown of cysteine-rich angiogenesis inducer (CCN1) could reduce the induction of EC inflammation and apoptosis by PA through inactivation of Wnt/β-catenin. 272 Low stress activates Wnt/β-catenin and promotes endothelial mesenchymal transition (EndMT). 273 …”
Section: Signaling Pathways In Atherosclerosismentioning
confidence: 99%
“…Gan et al found that the inhibition of Wnt/β-catenin signaling also reduced CCN1 expression, which led to endothelial cell inflammation and apoptosis. 28 Moreover, CCN1 promotes lipid accumulation and foam cell formation by impairing ATP-binding cassette transporters A1 and G1 (ABCA1/G1) mediated cholesterol efflux in macrophages. 29 In endothelial cells, CCN1 regulates cholesterol metabolism to allow ox-LDL to enter the stroma.…”
Section: Endothelial Mechanosensitive Genes In Asmentioning
confidence: 99%